Second Image IPE - Nölke, Andreas. author. aut Link
XXIII, 270 p. 13 illus.
Keywords: This book argues that the lack of adequate theories of contemporary capitalism is due to the increasing separation of the sub-disciplines of Comparative and International Political Economy. Theorizing only takes place in one of the two over-specialized sub-disciplines of Political Economy, thereby leading to a neglect of the interplay between national and international dimensions of capitalism. The author seeks to rectify this gap by developing a theory of Second Image IPE. Based on the “second image” notion developed by Kenneth Waltz, he furthers the classical theoretical approaches as developed by Peter Gourevitch and Peter Katzenstein. For this purpose, he incorporates recent analytical developments in Comparative Capitalism and Growth Model analysis. The book demonstrates the usefulness of Second Image IPE theory by studying the major empirical topics of Global Political Economy, including security, finance, regional integration, trade, production and global order. It also covers recent issues such as deep integration, selective de-globalization and state capitalist challenges to liberal international institutions. Andreas Nölke is Professor of Political Science at Goethe University Frankfurt, Germany. His recent books include Post-Corona Capitalism: The Alternatives Ahead (Bristol University Press, 2022) and State-Permeated Capitalism in Large Emerging Economies (Routledge, 2020, co-authored). For Second Image IPE, he has received an Opus Magnum grant by the Volkswagen Foundation.